2019
DOI: 10.1016/j.neubiorev.2018.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Why would Parkinson’s disease lead to sudden changes in creativity, motivation, or style with visual art?: A review of case evidence and new neurobiological, contextual, and genetic hypotheses

Abstract: Parkinson's disease (PD) is a devastating diagnosis with, however, potential for an extremely intriguing aesthetic component. Despite motor and cognitive deficits, an emerging collection of studies report a burst of visual artistic output and alterations in produced art in a subgroup of patients. This provides a unique window into the neurophysiological bases for why and how we might create and enjoy visual art, as well as into general brain function and the nature of PD or other neurodegenerative diseases. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 200 publications
2
17
0
Order By: Relevance
“…Evidence suggests connections to increased felt reward, heightened impulsivity and creativity, or lowered inhibition, with patients reporting feeling freer, more spontaneous (Chatterjee et al, 2006;Lhommée et al, 2014;Pinker, 2002;Walker, Warwick, & Cercy, 2006), and often reporting a needed outlet for their creative expression (Kulisevsky, Pagonabarraga, & Martinez-Corral, 2009). This is also supported by some empirical comparisons using standardized visual and non-visual/verbal measures (Canesi, Rusconi, Isaias, & Pezzoli, 2012, Canesi et al, 2016, with such changes typically suggested to relate to DA-related or other functional changes throughout the mesolimbic reward and prefrontal mesocortical regions (Lauring et al, 2019).…”
Section: Hypotheses and Outstanding Questions For The Impact Of Pd Onmentioning
confidence: 89%
See 4 more Smart Citations
“…Evidence suggests connections to increased felt reward, heightened impulsivity and creativity, or lowered inhibition, with patients reporting feeling freer, more spontaneous (Chatterjee et al, 2006;Lhommée et al, 2014;Pinker, 2002;Walker, Warwick, & Cercy, 2006), and often reporting a needed outlet for their creative expression (Kulisevsky, Pagonabarraga, & Martinez-Corral, 2009). This is also supported by some empirical comparisons using standardized visual and non-visual/verbal measures (Canesi, Rusconi, Isaias, & Pezzoli, 2012, Canesi et al, 2016, with such changes typically suggested to relate to DA-related or other functional changes throughout the mesolimbic reward and prefrontal mesocortical regions (Lauring et al, 2019).…”
Section: Hypotheses and Outstanding Questions For The Impact Of Pd Onmentioning
confidence: 89%
“…Within the above PD symptoms and stages, researchers have begun uncovering intriguing indication for impact on art or aesthetic processing/experience (see again also Figure 1). This is noted primarily in case studies or anecdotal reports involving art production and changes in the output of artists (Inzelberg, 2013;Lauring et al, 2019), and may suggest at least potential reciprocal effects on art viewing or aesthetic appreciation.…”
Section: Hypotheses and Outstanding Questions For The Impact Of Pd Onmentioning
confidence: 99%
See 3 more Smart Citations